ANALISIS WACANA KRITIS PADA PIDATO POLITIK MANTAN KETUA UMUM PARTAI GOLKAR ABURIZAL BAKRIE (CRITICAL DISCOURSE ANALYSIS ON POLITICAL SPEECH BY THE FORMER HEAD OF GOLKAR, ABU RIZAL BAKRIE) - Herlina Yuni Astuti (Universitas Lambung Mangkurat, 2020)
AbstractCritical Discourse Analysis on Political Speech by The Former Head of Golkar,Abu Rizal Bakrie. Discourse is a unit of language based on words used tocommunicate in social contexts. Therefore, it cannot be denied that language isan effective tool in all aspects of life, including on the political stage. This studyaims to analyze the structure of the political speech of the former chairman of theGolkar Party, Aburizal Bakrie, entitled